A tragédia nos escritos de 1797-1800 de Friedrich Holderlin - Carolina Meire de Faria (2021)
This work aims to highlight, in the writings from 1797 to 1800 and in the unfinished play The Death of Empedocles, as Friedrich Hölderlin would be simultaneously postulating a poetics - study of literary genres - and a philosophy of the tragic. This is intends to show how, in the hölderlinian work, in addition to poetry, literary genres are intertwined in order to constitute a medium for reflection on philosophical issues. Through such a gesture, that is, to make poetry and poiesis a praxis of thought, the poet articulates one of the central themes of 18th century German thought, namely, what is the best way to read and translate “'the spirit and the Greek letters'”. It is observed that this relationship imposes its presence in several areas of the philosophy of the time, be it in aesthetics (mimesis, the figure of the genius, the tekhné), in political philosophy (law, freedom, state) or in the philosophy of nature (man, senses of nature and, to some extent, physis). In this way, figures such as Homer, Sophocles, Socrates, Plato and Aristotle are widely contemplated in the hölderlinian literature. In the case of the play The Death of Empedocles, it is suggested, as a hypothesis, that Hölderlin chooses tragedy as a literary genre in order to dramatize the appropriations of the Greeks carried out by German classicism/ romanticism, differing from these movements and contributing to the thought of his time. In order to support this interpretative proposal, were mobilized, in addition to the dramatic text, the complete correspondence and textual fragments of the poet elaborated in 1797 to 1800, in which reflections are observed between his project of tragedy and his poetics of thought.